Climate adaptation and job prospects for young people in agriculture - Cenacchi, Nicola; Brooks, Karen; Dunston, Shahnila; Wiebe, Keith D.; Arndt, Channing; Hartley, Faaiqa; Robertson, Richard D. (International Food Policy Research Institute, 2020)
According to the United Nations, the world’s population will grow by 2 billion people over the coming decades to reach 9.7 billion by 2050 (UNDESA-DP 2019a). The dignity and life prospects of those additional 2 billion people will depend on their ability to meet basic needs, such as food, clothing, and shelter, and their access to adequate employment. The most pressing need for jobs will be felt in those regions and countries that have not yet gone through the demographic transition, and where the cohort of young people is growing rapidly. The challenge will be compounded by an increasingly crowded, more competitive world with fewer natural resources per capita, and by the threat of climate change, which is projected to affect every sector of the economy (Arent 2014).